Inflation targeting policy as a framework for managing monetary policy in Sudaneconometrics study during the period (1980-2018) With reference to the experiences of some leading countries - sery, Sammar Hussain; Elfaki, Mansour Ahmed (Journal of Economic, Administrative and Legal Sciences, 2021)
Targeting inflation is ultimate goal of monetary policy as this policy is expected to control inflation and maintain economic growth. The experiences of developing countries have shown that the inflation targeting mechanism is an effective system for managing monetary policy in its endeavor to achieve general price stability Studies on Sudan have shown that structural economic imbalances, underdevelopment of the financial and banking sector, and poor coordination between monetary and fisical policies remain an obstacle to developing a framework for targeting inflation. maintaining a low and stable rate of inflation in the long term. The study assumed that government spending is not an independent policy tool to control inflation, and there is an inverse relationship between GDP and inflation. The study findings show the existence of two cointegration vectors for inflation and its determinants, and the insignificance of the money supply and government spending. The study recommended not adopting expansionary monetary policies reducing government spending, especially current spending, and improving the exchange rate in the country by subsidizing and diversifying its production to increase GDP and encourage exports.
Keywords: inflation; exchange rate; money supply; Sudan; Johansson's symmetric integration model